The Impact of the Covid-19 Pandemic on the World of Education in Indonesia - Novianita Rulandari (Yayasan Ilomata, 2020)
Since the beginning of 2020, the world has been shocked by the Corona Virus Diseases (Covid-19) pandemic which has spread rapidly throughout the world, infecting more than forty million people, causing more than one million deaths by October 2020. This pandemic has an impact on the education world where all levels of education from kindergarten to postgraduate are required to carry out distance learning through online-based classes. Various problems then arise in distance learning because not all students have the facilities and infrastructure needed in its implementation, even causing casualties. This research examines and discusses the phenomenon of Covid-19 pandemic and its impact on the education world in Indonesia. The purpose of this research is to find out government policies in overcoming learning problems in a pandemic situation and finding the right policies so that learning can still be carried out effectively, how the supervision needs to be done by the government so that teaching and learning activities can run effectively and how the teaching communication strategies in using online media so that the delivery of material by lecturers can be easily understood by students. From the research results, several conclusions were obtained. The Minister's policy to carry out the online learning process still faces various challenges in its implementation; The learning process from home must always be monitored through good cooperation between students, parents, and educators, especially for primary and secondary education; and by using some appropriate learning communication strategies, the online teaching and learning process can be carried out more effectively because it does not take up a lot of time and space.